PEMBERDAYAAN KADER DALAM MENINGKATAN KEMAMPUAN SISWA PMR DALAM PENANGANAN PERTAMA LUKA BAKAR - Rachmania, Diana; kartika sari, Melani; Susmiatin, Eko Arik (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Burns are a form of trauma that occurs as a result of human activities in the household, industry, traffic accidents, or natural disasters they can happen to anyone who is at high risk of experiencing burns. Inappropriate knowledge and actions in providing wound care can disrupt wound healing or even cause infection.  This community service activity aims to improve the ability of PMR students how to first treat burns quickly and appropriately. The method used in this service activity is empowerment and delivering material through lectures and discussions. The empowerment method is carried out by selecting health cadres to present material that has been prepared by the service team. The selected cadre is the Chair of the PMR at SMAN 1 Plosoklaten Kediri, then the selected cadre delivers the material again to all participants in community service activities, namely all PMR members. The number of respondents was 30 students who were members of PMR. The ability to first treat burn wounds was measured before and after the activity. The instrument used was a questionnaire. The results of activities before the intervention showed that almost half (40%) of respondents had abilities in the sufficient category. After service activities, it was found that some respondents (50%) had good abilities. There was an increase in the ability of PMR members to treat burns from the results before and after the activity. It is hoped that PMR students will be able to apply the material taught by the presenters so that PMR students can carry out the first treatment of burn wounds independently.